Mark D. Anderson. Disaster Writing: The Cultural Politics of Catastrophe in Latin America. Charlottesville: U of Virginia P, 2011. 241 pp. - Nicasio Urbina (Studies in 20th & 21st Century Literature, 2014)
Review of Mark D. Anderson. Disaster Writing: The Cultural Politics of Catastrophe in Latin America. Charlottesville: U of Virgina P, 2011. 241 pp.
Keywords: Latin American literature; natural disasters